An Experimental Investigation on Dynamic Characteristics of Soft Soils Treated by Vibration-Drainage Method - Jie Yin; Yong Tang; Yong-hong Miao; Ruo-yu Sheng (Advances in Civil Engineering)
This paper presents an experimental investigation on the dynamic characteristics of soft soils that are treated by vibration-drainage method (VDM). The representative dynamic axial strain at a given number of cycles was obtained. The VDM-treated soft soil exhibited different dynamic deformation characteristics that are not only affected by the cyclic frequency but also influenced by the vibration frequency during the treatment process. Soil specimens at different cyclic frequencies show a similar variation trend that the axial strain systematically grows with increasing number of cycles. The rate of axial strain for all specimens systematically linearly decreases with the increase of number of cycles in the log-log scale. Results showed that both axial strain and strain rate exhibit relatively lower values at a given number of cycles under the condition that the applied cyclic frequency is equal to vibration frequency. It is expected that the soil structure will be more stable if the applied cyclic frequency is close to the vibration frequency that is applied on VDM-treated soil. Therefore, the vibration frequency close to the possible dynamic loading frequency is recommended in the process of soft soil improvement via VDM in the related engineering applications.